CP-008 A clinico-ethical framework for multidisciplinary medicines review in nursing homes: a health foundation shine project. (24th March 2015) - Campbell, D; Baqir, W; Barrett, S; Desai, N; Hughes, J; Copeland, R; Laverty, A; Mackintosh, J
Abstract : Background: Polypharmacy is common in care home residents. Inappropriate and potentially harmful prescribing in older people has been reported extensively in the literature. Residents in care homes often have little involvement in prescribing decisions involving them. Reviewing and stopping inappropriate medicines is not standard practice across the health economy. Purpose: To develop a method of optimising medicines whilst ensuring that all residents were involved in decisions. Material and methods: Pharmacists undertook a detailed medicines review using primary care records and presented to a multidisciplinary team (MDT) meeting with the care home nurse and general practitioner. The team considered: Is the medicine still needed? Is the medicine beneficial, taking into account co-morbidities? Are any appropriate medicines not being prescribed? Following the MDT meeting, residents were asked their views before any intervention was made. Residents were followed up after the review to identify any adverse events. Any residents taking psychotropic medicines were discussed with a Psychiatry of Old Age Services consultant where appropriate. Results: In total 422 residents in 20 care homes were reviewed; 1, 346 interventions were made in 384 (91%) residents, with the most common intervention being to stop a prescription. 704 medicines were stopped in 298 residents. 1.7 medicines were stopped for every resident reviewed (range 0 to 9 medicines; SD 1.7), giving a 17.4% reduction in medicines prescribed. The main reasons for stopping medicines were a lack of current indication (57%) and residents not wanting to take the medicine (17%). 41 medicines (6%) were stopped because of safety concerns. Follow-up found 9 minor events following stopping medicines. The net annualised savings against the medicines budget were €99, 340 or €235 per resident reviewed. Conclusion: This project demonstrated that a multidisciplinary medicines review involving a pharmacist, doctor, care home nurse and the resident can safely reduce over-prescribing and inappropriate medication whilst generating significant savings from the medicines budget. References and/or acknowledgements: No conflict of interest.